2020
DOI: 10.3389/fphar.2020.00443
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Mastocytosis: Following the Tyrosine Kinase Inhibition Roadmap

Abstract: Systemic mastocytosis is a rare and heterogeneous disease characterized by mast cell proliferation and activation. KIT is a transmembrane tyrosine kinase which plays a key role in mast cell growth, differentiation and survival. After interaction with its ligand, the stem cell factor, KIT dimerizes activating downstream pathways involving multiple tyrosine kinases (PI3K, JAK/STAT, RAS/ERK). Activating mutations in KIT are detected in most cases of systemic mastocytosis, being the most common KIT D816V. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…The response rates were similar across sub-types, including in 16 patients with mast cell leukemia (MCL) [ 121 ]. The selective KIT D816V inhibitor avapritinib was recently FDA-approved for the treatment of ASM in June 2021 based on the emerging results of the phase I EXPLORER trial and phase II PATHFINDER trial [ 122 , 123 ]. At an interim analysis of the phase II PATHFINDER trial, ORR was 75%, and there was no observed difference in response rates between previously treated and untreated patients, including those receiving prior midostaurin therapy [ 122 ].…”
Section: Management Of Mast Cell Disordersmentioning
confidence: 99%
“…The response rates were similar across sub-types, including in 16 patients with mast cell leukemia (MCL) [ 121 ]. The selective KIT D816V inhibitor avapritinib was recently FDA-approved for the treatment of ASM in June 2021 based on the emerging results of the phase I EXPLORER trial and phase II PATHFINDER trial [ 122 , 123 ]. At an interim analysis of the phase II PATHFINDER trial, ORR was 75%, and there was no observed difference in response rates between previously treated and untreated patients, including those receiving prior midostaurin therapy [ 122 ].…”
Section: Management Of Mast Cell Disordersmentioning
confidence: 99%
“…Oncogenic KIT mutations often occur in malignancies such as GISTs and mastocytosis [ 3 , 7 ], and our previous studies suggested that KIT mutants mediated distinct signaling pathways in addition to the ligand-independent activation [ [20] , [21] , [22] ]. In order to know whether PTPRE attenuates the activation of KIT mutants similarly as wild-type KIT, we further studied the function of PTPRE on the activation of KIT mutation D816V which is the most often happened mutation in mastocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…KIT is a receptor tyrosine kinase that plays an important role in hematopoiesis, gametogenesis and melanogensis, and oncogenic KIT mutations have been identified in GISTs, mastocytosis, acute myeloid leukemia, melanoma and others [ [1] , [2] , [3] , 7 , 23 , 24 ]. Signaling studies of wild-type KIT and KIT mutants have showed that KIT mutants have different signaling properties in addition to the ligand independent activation which was considered as the main cause of cell transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Tyrosine kinase inhibitors (TKI) like Masitinib, Imatinib or Midostaurin have demonstrated clinical activity in systemic mastocytosis, by blocking MC activation/proliferation. 11,12 Thus, it is tempting to suggest that TKI with high safety profiles may be used in SpA to block joint inflammation as it has been reported in RA. 13,14 Overall, although fundamental studies are required to clarify the role of MCs in SpA, we can conclude that these innate immune cells are not simple inflammatory bystanders but rather drivers of pain and inflammation.…”
mentioning
confidence: 99%